INTEGRATING GREEN CHEMISTRY AND QUALITY BY DESIGN: DEVELOPMENT OF A NOVEL STARCH-BASED MICROCOMPOSITE SYSTEM FOR PROLONGED CAPTOPRIL DELIVERY AND FLATTENED PHARMACOKINETICS - DINESH L BAWANKAR; UJWAL B VYAS (Asian Journal of Pharmaceutical and Clinical Research, 2026)
Objectives: The goal of this work was to form a new once-a-day oral dosage form (microcomposite beads) for the blood pressure drug Captopril that releases the medicine slowly, and that is built from a starch taken from plants by a low-impact “green” method. Methods: Tubers of Amorphophallus paeoniifolius (Elephant Foot Yam) were the starting material. A deep eutectic solvent made from glycerol and choline chloride pulled the native starch, which was then carboxymethylated to produce Carboxymethylated Elephant Foot Yam Starch (CM-EFYS) with 0.45±0.03 carboxymethyl groups per glucose unit. Fourier-transform infrared spectra showed new carboxylate bands, X-ray data showed a 46.7% drop in crystallinity, while swelling power rose by 77% and solubility by 133%. A quality-by-design approach with a full factorial design-of-experiments matrix was used to prepare drug-loaded beads by combining CM-EFYS with sodium alginate and cross-linking in calcium chloride. Results: The optimized formulation contained 3.2% w/v CM-EFYS, 3.1% w/v CaCl₂, and a polymer-to-drug ratio of 3.3:1, producing nearly spherical beads of 642±14 μm with 86.9±1.6% drug entrapment. The beads released Captopril gradually for 24 h and followed the Korsmeyer–Peppas model (R2=0.992, n = 0.689). In rabbits, the beads reduced the maximum plasma concentration (Cmax) by 62.2%, delayed time to Cmax (Tmax) from 2 h to 8 h, and increased mean residence time by 162.6%, while maintaining bioequivalent area under the curve. Six-month stability testing at 40°C and 75% relative humidity showed minimal potency loss when packed in foil. Conclusion: A functional polymer for once-daily sustained release of captopril was successfully created from green-extracted, CM-EFYS. The optimized formulation demonstrated high drug entrapment efficiency (86.9±1.6%) and controlled 24-h release following Korsmeyer–Peppas kinetics (R²=0.992, n=0.689). The formulation’s stability under accelerated conditions demonstrated its potential as an efficient and environmentally friendly sustained-release oral dosage system.